2018
DOI: 10.1002/14651858.cd007105.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetics and regional anaesthesia versus conventional analgesia for preventing persistent postoperative pain in adults and children

Abstract: We conclude that there is moderate-quality evidence that regional anaesthesia may reduce the risk of developing PPP after three to 18 months after thoracotomy and three to 12 months after caesarean section. There is low-quality evidence that regional anaesthesia may reduce the risk of developing PPP three to 12 months after breast cancer surgery. There is moderate evidence that intravenous infusion of local anaesthetics may reduce the risk of developing PPP three to six months after breast cancer surgery.Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
13

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 223 publications
(736 reference statements)
1
103
0
13
Order By: Relevance
“…Although poorly controlled acute postoperative pain has been implicated as a risk factor for the development of PPSP [51], there is no evidence to indicate that rebound pain per se predisposes to PPSP [13]. On the contrary, a recent Cochrane review reported that RA may instead reduce the incidence of PPSP after breast surgery and cesarean section [4]. As described above, the transitory nature of rebound pain, coupled with the early conduction block of nociceptive transmission, makes it unlikely that central sensitization will be exacerbated.…”
Section: Ppspmentioning
confidence: 99%
See 1 more Smart Citation
“…Although poorly controlled acute postoperative pain has been implicated as a risk factor for the development of PPSP [51], there is no evidence to indicate that rebound pain per se predisposes to PPSP [13]. On the contrary, a recent Cochrane review reported that RA may instead reduce the incidence of PPSP after breast surgery and cesarean section [4]. As described above, the transitory nature of rebound pain, coupled with the early conduction block of nociceptive transmission, makes it unlikely that central sensitization will be exacerbated.…”
Section: Ppspmentioning
confidence: 99%
“…Regional anesthesia (RA) techniques have been shown to reduce perioperative opioid requirements [ 1 ], postoperative length of stay [ 2 , 3 ], and positively impact long-term outcomes such as the risk of persistent postsurgical pain (PPSP) [ 4 ], morbidity, and mortality [ 5 ]. RA is thus an important component of multimodal anesthetic and analgesic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a strong body of evidence also supports the use of thoracic epidural anaesthesia and PVB. A lower‐risk of postoperative pulmonary complications and chronic pain has been reported when epidural analgesia was provided in patients undergoing open thoracotomy . More recently, PVBs have become more popular given their simplicity (insertion under ultrasound‐guidance or visual control by the surgeon), safety and effectiveness.…”
Section: Impact Of Anaesthetists and Anaesthetic Techniquementioning
confidence: 99%
“…2 A reduction in the incidence of persistent postoperative pain, with the use of regional anesthesia or local anesthetic infusions, has been reported for thoracotomy, caesarean section and breast cancer surgery. 3 Furthermore, exclusive use of opioids for perioperative pain has become a controversial issue. Between 1999 and 2016, more than 630,000 people died from a drug overdose in the United States.…”
mentioning
confidence: 99%